PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN ECENG GONDOK DI DESA KESONGO KECAMATAN TUNTANG KABUPATEN SEMARANG - Vinsensia Apriliana Crisindi; R. Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Rawa Pening in Semarang Regency is one of the national priority lakes based on Presidential Regulation No. 60 of 2021. The main problem faced is the massive growth of water hyacinth due to human activities around the lake, which has an impact on siltation and disrupts the economic activities of the community. The Kesongo Village Government is trying to overcome this problem through community empowerment based on local potential, one of which is by supporting the development of Bengok Craft as an MSME business that processes water hyacinth into value-added products. This study aims to analyse the community empowerment process carried out by the village government and identify the supporting and inhibiting factors. The method used is descriptive qualitative through observation, interviews, and documentation. The results show that empowerment is carried out through the stages of awareness raising, capacity building, and empowerment. Supporting factors include the availability of raw materials, production facilities and infrastructure, as well as functioning organisations and administration. Meanwhile, inhibiting factors include limited human resource quality, weak supporting institutions, and the lack of adequate village government policies. This study concludes that Bengok Craft has the potential to be a dual solution, namely controlling water hyacinth and empowering the community economically, but it still requires institutional strengthening and the formulation of village policies in order to run more optimally and sustainably.